ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS DESA PARIGI KECAMATAN CIKANDE - Ramdani, Febryan Ajeng (Ensiklopedia Sosial Review, 2025)
: This study aims to analyze the level of community satisfaction with health services at Puskesmas Desa Parigi, Cikande District, using the SERVQUAL model which includes five dimensions: Reliability, Responsiveness, Assurance, Empathy, and Physical Facilities. The research method used is a quantitative approach by distributing questionnaires to 100 respondents. The results showed that the Empathy dimension obtained the highest score (63%), indicating that the attention of health workers to the special needs of patients is a major strength in service. The Physical Facilities and Reliability dimensions each scored 61%, reflecting that the physical facilities and consistency of service are adequate, although there is still room for improvement. The Responsiveness dimension scored 60%, with particular attention to improving communication regarding service procedures. The Assurance dimension obtained the lowest score (59%), indicating that aspects of protecting the confidentiality of information and patient safety need to be improved. Overall, health services at the Parigi Village Health Center have provided a fairly good level of satisfaction, but still require improvement in several aspects, such as service consistency, privacy protection, and comfort of physical facilities. The findings provide practical implications in the form of recommendations for improving operational management, communication training, and renovating physical facilities to improve the quality of health services.Keywords: Analysis; Public Satisfaction; Public Service; Health.